Congenital myasthenic syndrome caused by a frameshift insertion mutation in GFPT1. (August 2020) - Szelinger, Szabolcs; Krate, Jonida; Ramsey, Keri; Strom, Samuel P.; Shieh, Perry B.; Lee, Hane; Belnap, Newell; Balak, Chris; Siniard, Ashley L.; Russell, Megan; Richholt, Ryan; Both, Matt De; et al.
Abstract : Objective: Description of a new variant of the glutamine-fructose-6-phosphate transaminase 1 ( GFPT1 ) gene causing congenital myasthenic syndrome (CMS) in 3 children from 2 unrelated families. Methods: Muscle biopsies, EMG, and whole-exome sequencing were performed. Results: All 3 patients presented with congenital hypotonia, muscle weakness, respiratory insufficiency, head lag, areflexia, and gastrointestinal dysfunction. Genetic analysis identified a homozygous frameshift insertion in the GFPT1 gene (NM_001244710.1: c.686dupC; p.Arg230Ter) that was shared by all 3 patients. In one of the patients, inheritance of the variant was through uniparental disomy (UPD) with maternal origin. Repetitive nerve stimulation and single-fiber EMG was consistent with the clinical diagnosis of CMS with a postjunctional defect. Ultrastructural evaluation of the muscle biopsy from one of the patients showed extremely attenuated postsynaptic folds at neuromuscular junctions and extensive autophagic vacuolar pathology. Conclusions: These results expand on the spectrum of known loss-of-function GFPT1 mutations in CMS12 and in one family demonstrate a novel mode of inheritance due to UPD.